Prososial, Ketangguhan dan Kesejahteraan Mental: Studi Komparatif berdasarkan Preferensi Kader Tiwisada - Wahyu Pujianto; Adi Sucipto; Harun Ahmad (Pusat Riset dan Inovasi Nasional, 2026)
Late childhood through early adolescence is a crucial period of psychosocial development, during which individuals begin to form self-identities, develop more complex social relationships, and build resilience and mental well-being. In elementary schools, the School Health Unit (UKS) plays a strategic role in shaping students' character and healthy behaviors. One example is the Tiwisada Cadre program, which involves young health cadres trained to assist with promotive and preventive activities within the school environment. The purpose of this study was to determine the differences in prosocial behavior, resilience, and mental well-being between UKS Tiwisada cadres and non-Tiwisada cadres at SDN Panggungrejo 04 Kepanjen. This study used an ex post facto approach, which is methodologically similar to experimental research that tests hypotheses. However, in ex post facto research, the researcher does not administer any specific treatment or manipulation, as the event occurred prior to the study. The population in this study were all students at SDN Panggungrejo 04 Kepanjen, Malang Regency, who have the Tiwisada Cadre extracurricular program. The sample size was 104 students, with each group consisting of 52 Tiwisada Cadres and 52 non-Tiwisada Cadres. The results showed that there were significant differences in prosocial behavior, resilience, and mental well-being between Tiwisada UKS cadres and non-cadres. Tiwisada cadres tended to have different results in terms of prosocial behavior, resilience, and mental well-being that were higher than non-cadres. The conclusion of this study is that there are significant differences in prosocial behavior, resilience, and mental well-being between Tiwisada UKS cadres and non-cadres. Cadres showed higher levels of prosocial behavior, resilience, and mental well-being than non-cadres.